1999
DOI: 10.1115/1.1314609
|View full text |Cite
|
Sign up to set email alerts
|

Recommendations for Achieving Accurate Numerical Simulation of Tip Clearance Flows in Transonic Compressor Rotors

Abstract: The tip clearance flows of transonic compressor rotors are important because they have a significant impact on rotor and stage performance. A wall-bounded shear layer formed by the relative motion between the overtip leakage flow and the shroud wall is found to have a major influence on the development of the tip clearance flow field. This shear layer, which has not been recognized by earlier investigators, impacts the stable operating range of the rotor. Simulation accuracy is dependent on the ability of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(30 citation statements)
references
References 17 publications
0
29
0
Order By: Relevance
“…Since this is a single-stage facility, a rotor-only configuration was used to accurately get experimental measurements for R35 alone [14]. In this rotor-only configuration the R35, with a design speed of 17,194 rpm and aspect ratio of 1.19, was run at 80% design speed due to rotor/stator matching requirements for a follow-up stage investigation [14]. Data capture for the 80% design speed at peak efficiency occurred at a tip speed of 363 m/s and a total pressure ratio of 1.44.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this is a single-stage facility, a rotor-only configuration was used to accurately get experimental measurements for R35 alone [14]. In this rotor-only configuration the R35, with a design speed of 17,194 rpm and aspect ratio of 1.19, was run at 80% design speed due to rotor/stator matching requirements for a follow-up stage investigation [14]. Data capture for the 80% design speed at peak efficiency occurred at a tip speed of 363 m/s and a total pressure ratio of 1.44.…”
Section: Methodsmentioning
confidence: 99%
“…Grid cells in this region maintain a size ratio of 1.0 across the tip into the gap and cluster as they approach the shroud. A configuration such as this treats the tip region simply as an inviscid region where no changes take place in mass, momentum, or energy and the boundaries are periodic [14]. Construction of the twelve and four blade passage grids was a relatively simple process.…”
Section: Blockmentioning
confidence: 99%
“…The ability of the APNASA code to predict the stalling mass flow rate for an isolated transonic rotor (R35) has been demonstrated by Van Zante, et al (1999), see Figure 1. Van Zante, et al concluded that accurate prediction of the stable operating range requires careful attention to grid resolution near the casing.…”
Section: Computationally Based Studymentioning
confidence: 99%
“…The rotor had 9 cells and the stator had 8 cells across the clearance gap at the casing. The cells were packed at the casing in both blade rows to capture the wall bounded shear layer so that the rotor tip clearance flow is accurately simulated [17]. The rotor had 51 nodes and the stator 79 nodes in the circumferential direction.…”
Section: Numerical Codesmentioning
confidence: 99%